White matter microstructure in youths with conduct disorder: effects of sex and variation in callous traits - Rogers, Jack C.; Kirchner, Marietta (Journal of the American Academy of Child and Adolescent Psychiatry, 2019)
Studies using diffusion tensor imaging (DTI) to investigate white matter (WM) microstructure in youths with conduct disorder (CD) have reported disparate findings. We investigated WM alterations in a large sample of youths with CD, and examined the influence of sex and callous-unemotional (CU) traits. Method DTI data were acquired from 124 youths with CD (59 female) and 174 typically developing (TD) youths (103 female) 9 to 18 years of age. Tract-based spatial statistics tested for effects of diagnosis and sex-by-diagnosis interactions. Associations with CD symptoms, CU traits, a task measuring impulsivity, and the impact of comorbidity, and age- and puberty-related effects were examined. Results Youths with CD exhibited higher axial diffusivity in the corpus callosum and lower radial diffusivity and mean diffusivity in the anterior thalamic radiation relative to TD youths. Female and male youths with CD exhibited opposite changes in the left hemisphere within the internal capsule, fornix, posterior thalamic radiation, and uncinate fasciculus. Within the CD group, CD symptoms and callous traits exerted opposing influences on corpus callosum axial diffusivity, with callous traits identified as the unique clinical feature predicting higher axial diffusivity and lower radial diffusivity within the corpus callosum and anterior thalamic radiation, respectively. In an exploratory analysis, corpus callosum axial diffusivity partially mediated the association between callous traits and impulsive responses to emotional faces. Results were not influenced by symptoms of comorbid disorders, and no age- or puberty-related interactions were observed. Conclusion WM alterations within the corpus callosum represent a reliable neuroimaging marker of CD. Sex and callous traits are important factors to consider when examining WM in CD.